Development Of Hardware and Software For A NonInvasive Glucometer Based On A Microcontroller (Texas Journal of Medical Science, 2024)
In modern medical practice, there is a tendency to widely use non-invasive methods of monitoring and diagnosing patients. Diabetes is known to be the main cause of many types of severe diseases and if the patient is not properly taken care of in a timely manner, it eventually leads to death. This disease occurs when blood glucose levels exceed a threshold value. Therefore, regular monitoring of blood glucose levels is a prerequisite for caring for patients with diabetes. Current methods for testing blood glucose levels are invasive methods that rely on needles that are inserted into a person's body to take a blood sample from the body, which is then transferred to disposable test strips for a chemical treatment to determine the amount of glucose present. However, attempts to relieve patient pain and discomfort have led to the development of non-invasive methods for controlling sugar levels. These methods use a near-infrared sensor to detect glucose levels from your fingertip without the use of needles or test strips. A near-infrared (NIR) optical signal is transmitted through one side of the fingertip and then received at the other side, which predicts the molecular count of blood glucose by analyzing the change in intensity of the received signal after its passage. In this work, we developed such a system using a microcontroller and other electronic parts. Before this, we developed a simulation model in the Proteus environment